Genomics of Secondarily Temperate Adaptation in the Only Non-Antarctic Icefish. (21st February 2023) - Rivera-Colón, Angel G; Rayamajhi, Niraj; Minhas, Bushra Fazal; Madrigal, Giovanni; Bilyk, Kevin T; Yoon, Veronica; Hüne, Mathias; Gregory, Susan; Cheng, C H Christina; Catchen, Julian M
Abstract: White-blooded Antarctic icefishes, a family within the adaptive radiation of Antarctic notothenioid fishes, are an example of extreme biological specialization to both the chronic cold of the Southern Ocean and life without hemoglobin. As a result, icefishes display derived physiology that limits them to the cold and highly oxygenated Antarctic waters. Against these constraints, remarkably one species, the pike icefish Champsocephalus esox, successfully colonized temperate South American waters. To study the genetic mechanisms underlying secondarily temperate adaptation in icefishes, we generated chromosome-level genome assemblies of both C. esox and its Antarctic sister species, Champsocephalus gunnari . The C. esox genome is similar in structure and organization to that of its Antarctic congener; however, we observe evidence of chromosomal rearrangements coinciding with regions of elevated genetic divergence in pike icefish populations. We also find several key biological pathways under selection, including genes related to mitochondria and vision, highlighting candidates behind temperate adaptation in C. esox . Substantial antifreeze glycoprotein (AFGP) pseudogenization has occurred in the pike icefish, likely due to relaxed selection following ancestral escape from Antarctica. The canonical AFGP locus organization is conserved in C. esox and C. gunnari, but both show a translocation of two AFGP copies to a separate locus, previously unobserved in cryonotothenioids. Altogether, the study of this secondarily temperate species provides an insight into the mechanisms underlying adaptation to ecologically disparate environments in this otherwise highly specialized group.